GANGA AND YAMUNA AT THE TEMPLE THRESHOLD: AN ICONOGRAPHIC AND SPATIAL STUDY - Sokhi, Simer Preet; Vats, Parul Purohit (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
This paper analyses the placement of the river goddesses Ganga and Yamuna at temple thresholds through formal, spatial, and ritual frameworks, situating their imagery within Vedic, epic, and Puranic traditions where both function as agents of purification and auspicious transition. It examines sculptural programmes at the entrance to the garbhagriha, focusing on doorjamb reliefs in which Ganga is marked by the makara and Yamuna by the kurma, each attended by subsidiary figures, their forms carved along the doorjambs in positions that flank and define the axis of entry. A spatial reading of this arrangement shows that the doorway operates as a regulated threshold that directs bodily movement rather than a neutral opening; the consistent placement of these figures on the lower sections of the doorframe establishes a visual and ritual field that must be crossed before access to the sanctum. Their iconographic attributes and fixed location structure a sequence in which entry aligns with the logic of ablution, allowing the threshold to be read as a tirtha, a point of crossing where movement acquires ritual value. Passing between Ganga and Yamuna produces a transition analogous to river bathing and prepares the devotee for proximity to the deity, which supports the argument that these figures function as mediating agents within a spatial system that encodes purification into the act of entry and shapes the experience of sacred space.